2015
DOI: 10.1371/journal.pone.0119587
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of Advanced Glycation End-Products and Activation of the SCAP/SREBP Lipogenetic Pathway Occur in Diet-Induced Obese Mouse Skeletal Muscle

Abstract: Aim of this study was to investigate whether advanced glycation end-products (AGEs) accumulate in skeletal myofibers of two different animal models of diabesity and whether this accumulation could be associated to myosteatosis. Male C57Bl/6j mice and leptin-deficient ob/ob mice were divided into three groups and underwent 15 weeks of dietary manipulation: standard diet-fed C57 group (C57, n = 10), high-fat high-sugar diet-fed C57 group (HFHS, n = 10), and standard diet-fed ob/ob group (OB/OB, n = 8). HFHS mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
66
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(70 citation statements)
references
References 49 publications
4
66
0
Order By: Relevance
“…As both SREBP-1C and PPARg expression and the expression of their target genes are decreased, this suggests an inhibitory effect of PM on adipogenesis, possibly via the inhibition of SREBP-1C. In the literature, it has been described that the AGE N(e)-(carboxymethyl) lysine (CML) interferes with the SCAP/SREBP-1C pathway (17,18). In our study, we did not find any effect of PM on mRNA expression levels of SCAP in adipocytes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As both SREBP-1C and PPARg expression and the expression of their target genes are decreased, this suggests an inhibitory effect of PM on adipogenesis, possibly via the inhibition of SREBP-1C. In the literature, it has been described that the AGE N(e)-(carboxymethyl) lysine (CML) interferes with the SCAP/SREBP-1C pathway (17,18). In our study, we did not find any effect of PM on mRNA expression levels of SCAP in adipocytes.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we did not find any effect of PM on mRNA expression levels of SCAP in adipocytes. However, in different cell types CML has been described to colocalize with SCAP (17)(18)(19), suggesting a considerable glycation of SCAP, and consequently leading to altered function of SCAP. Therefore, the glycation of SCAP, along with the possible direct effects of PM, may be a possible mechanism by which AGEs enhance adipogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Only a few rodent models have been used to specifically study glycation. Of note are the chemically induced type 1 diabetes (T1D) models, generated by administering streptozotocine (STZ); the genetically induced models of obesity with spontaneous T2D obtained by monogenic mutation, such as the Lep ob/ob mice (deficient in leptin) and the LepR db/db mice (lacking the functional, full‐length Ob‐Rb leptin receptor); and the diet‐induced obesity models (DIO) raised on a high fat (HF) or a high fat‐high sucrose diet (HF‐HS) …”
Section: Introductionmentioning
confidence: 99%
“…Among the DIO models of T2D, HF and HF‐HS diets have successfully rendered the animals intolerant to glucose but have mixed results with respect to inducing hyperglycaemia. Very few studies have used DIO models to observe the accumulation of AGEs in fluids, tissues, and organs …”
Section: Introductionmentioning
confidence: 99%
“…Although a recent study showed that 16 weeks on a HFD decreased the number of type IIb fibers and increased the number of type IIa fibers without assessing muscle contraction force (Mastrocola et al. ), the effect of a long‐term HFD on muscle fiber composition and muscle contractile force have not yet been fully elucidated.…”
Section: Introductionmentioning
confidence: 99%